2004
DOI: 10.1182/blood.v104.11.4521.4521
|View full text |Cite
|
Sign up to set email alerts
|

Safety Experience with Trisenox® (Arsenic Trioxide) Injection.

Abstract: Introduction: Trisenox®(arsenic trioxide) injection was approved in the United States in Sept 2000 and in the EU in March 2002 for the treatment of patients (pts) with relapsed or refractory acute promyelocytic leukemia (APL). Aim: The aim of this analysis is to assess the safety profile of Trisenox®. Methods: Safety information was gathered from monitored clinical trials and from spontaneous postmarketing reports. Results: As of June 2004, approximately 3600 pts had received comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The adverse events noted in postmarketing use of As 2 O 3 are generally similar to those observed in clinical trials, and no deaths due to As 2 O 3 related cardiac arrhythmia have been reported. This experience appears to confirm that As 2 O 3 is generally well tolerated and that the observed adverse effects are manageable and reversible [28] . However, when 7 patients with refractory or relapsed APL were treated with As 2 O 3 , 6 noted water retention (shown by weight gain, pleural and pericardial exudates); 2 of 3 patients on As 2 O 3 maintenance therapy showed polyneuropathy related to chronic arsenic poisoning, and 1 of those 2 patients suffered myoatrophy of a limb end [29] .…”
Section: Toxicity and Side Effectssupporting
confidence: 57%
“…The adverse events noted in postmarketing use of As 2 O 3 are generally similar to those observed in clinical trials, and no deaths due to As 2 O 3 related cardiac arrhythmia have been reported. This experience appears to confirm that As 2 O 3 is generally well tolerated and that the observed adverse effects are manageable and reversible [28] . However, when 7 patients with refractory or relapsed APL were treated with As 2 O 3 , 6 noted water retention (shown by weight gain, pleural and pericardial exudates); 2 of 3 patients on As 2 O 3 maintenance therapy showed polyneuropathy related to chronic arsenic poisoning, and 1 of those 2 patients suffered myoatrophy of a limb end [29] .…”
Section: Toxicity and Side Effectssupporting
confidence: 57%
“…However, because of its adverse effects and the emergence of new treatments, its use in treating these diseases has been avoided. Nonetheless, arsenic trioxide remains relevant, as in 2000, the FDA approved [61] this compound for use in the treatment of acute promyelocytic leukemia [34,62]. Paul Ehrlich, who is the "father of chemotherapy", having introduced the concepts of specific targets when developing new drugs, introduced Salvarsan in 1910 as an effective treatment for syphilis [35].…”
Section: Historical Timeline Of Anticancer Drugs: Casiopeínas ®mentioning
confidence: 99%